A big–data security mechanism based on fully homomorphic encryption using cubic spline curve public key cryptography. Issue 6 (18th August 2018) - Krishna, Addepalli V. N.
Abstract: In this work, a Cubic spline curve based Asymmetric mode encrypting data is used for Fully Homomorphic encryption on Big–Data. A steady state, one dimensional equation is integrated over a control volume to generate global variables. These global variables are used to calculate public key from chosen private key. Known the Public and private keys, the mechanism is used in providing security on Big data. The mechanism can be extended to Homorphic encryption where Arithmetic operations like addition and multiplication can be done on cipher texts without disturbing their integrity. Thus the proposed work supports the Security features even though the data is stored in Public Domain like cloud.